REDRESSING DIGITAL ORIENTALISM: VIETNAMESE CULTURAL PROFESSIONALS’ DIGITAL WORK DURING THE COVID-19 PANDEMIC - Duester, Emma; Teague, Michal (Animus. Revista Interamericana de Comunicação Midiática, 2021)
The current study investigates how digital technologies can potentially be used to re-orientate the global narrative on Vietnam, overcome an imbalance in representation and help redress digital orientalism. Global digital technologies allow Vietnamese cultural professionals to reach beyond the borders of their nation and to become part of the global art world. With this, they can participate in the production, dissemination, and circulation of discourses on art and culture globally. In doing so, they can redress digital orientalism by contemporizing narratives on Vietnam. However, there is an underlying tension, as the very means by which their voices are heard is achieved by using global (western) technologies, tools and platforms. The research uses a digital ethnography of the Facebook pages of 7 contemporary art spaces in Hanoi and 20 semi-structured interviews with art and cultural professionals in Hanoi. The interviews were carried out during the Covid-19 Pandemic and addressed its impact and use of digital technology in their work during this time.